Transoral endoscopic thyroid lobectomy and ipsilateral central neck lymph node dissection vestibular approach: analysis of the learning curve and clinical outcomes evaluation - Deng, Yuhang; Zhao, Jiaojiao; Tao, Mei; Zhao, Haixin; Fan, Ruoxin; Wang, Xiaoming; Lu, Xiubo (Frontiers in Endocrinology, 2025)
PurposeThe transoral endoscopic thyroidectomy vestibular approach (TOETVA) is distinguished by its ability to leave no visible scars on the body’s surface. Currently, there is still a lack of single-center large sample size analysis on the learning curve of TOETVA, especially for the treatment of thyroid cancer. This study aims to fill this void by presenting a comprehensive analysis of the learning curve and assessing the procedure’s feasibility in managing thyroid cancer.MethodsBetween June 2020 and June 2023, a retrospective analysis was conducted on 195 patients who had undergone the transoral endoscopic thyroidectomy vestibular approach (TOETVA) at the First Affiliated Hospital of Zhengzhou University. We employed the cumulative sum method (CUSUM) to delineate the learning curve of TOETVA. Additionally, clinical parameters across different stages of the learning process were meticulously compared and analyzed.ResultsAll patients successfully completed endoscopic surgery without conversion to open surgery. Utilizing the CUSUM algorithm, two distinct learning phases were delineated: the exploration phase, comprising 58 cases, and the maturation phase, encompassing 137 cases. Analysis revealed that the maturation phase demonstrated significantly reduced operative times (189.7 ± 237.27 vs. 138.15 ± 26.62 minutes, p<0.001), decreased blood loss (15.49 ± 15.05 vs. 9.67 ± 4.12 ml, p=0.005), and a lower incidence of complications (7 vs. 4, p=0.028) when compared to the exploration phase. Additionally, in the maturation phase, we achieved successful surgical outcomes in a subset of obese patients and those with nodular goiter.ConclusionTOETVA has been demonstrated to be safe and feasible, with the capability to effectively address complex cases once the learning curve has been surmounted.